Phenotypic Characteristics of Shahi Strain of Nagpuri Buffaloes in Chandrapur District of Maharashtra, India - Hamand, H.S.; Zinjarde, R.M.; Rokde, S.N.; Chore, N.S. (Journal of Buffalo Science, 2020)
Phenotypic Characterization of Shahi Strain of Nagpuri Buffaloes was done in the Chandrapur District of Maharashtra, India. Two hundred and forty Shahi strain of Nagpuri female buffaloes of various age groups were observed in their home tract (n farms=24). It was found that black coat colour, black coloured muzzle, white patches on the legs, whitish eyes, white coloured tail switch, horizontal ear orientation, sword-shaped horns with pointed tip first turning backwards and then upwards, bowl-shaped udder are typical characteristics of this breed. The average live body weight, body length, chest girth, height at withers, head length, breadth of head of these buffaloes is (means ± standard deviation) 433 ± 8.4 kg, 137.08 ± 2.78 cm 180.81 ± 3.84 cm, 129.43 ± 2.26 cm, 54.18 ± 1.10 cm, 28.18 ± 0.34 cm in 3 years and above age group, respectively. The average daily milk yield and milk yield per lactation of Shahi strain of Nagpuri buffaloes were observed to be 4.06 ± 0.08 kg and 1,220.84 ± 41.57 kg, respectively.